Conservation genomic study of Hopea hainanensis (Dipterocarpaceae), an endangered tree with extremely small populations on Hainan Island, China - Tang, Liang; Long, Jun-qiao; Wang, Hai-ying; Rao, Chao-kang; Long, Wen-xing; Yan, Li; Liu, Yong-bo (Frontiers in Plant Science, 2024)
Hopea hainanensis Merrill & Chun is considered a keystone and indicator species in the tropical lowland rainforests of Hainan Island. Due to its high-quality timber, H. hainanensis has been heavily exploited, leading to its classification as a First-Class National Protected Plants in China and a Plant Species with Extremely Small Populations (PSESP). This study analyzed genome-wide single nucleotide polymorphisms (SNPs) obtained through Restriction site-associated DNA sequencing (RAD-seq) from 78 adult trees across 10 H. hainanensis populations on Hainan Island. The nucleotide diversity of the sampled populations ranged from 0.00096 to 0.00138, which is lower than that observed in several other PSESP and endangered tree species. Bayesian unsupervised clustering, principal component analysis, and NJ tree reconstruction identified 3 to 5 genetic clusters in H. hainanensis, most of which were geographically widespread and shared by multiple populations. Demographic history analysis based on pooled samples indicated that the decline of the H. hainanensis population began approximately 20,000 years ago, starting from an ancestral population size of about 10,000 individuals. The reduction of population size accelerated around 4,000 years ago and has continued to the present, resulting in a severely reduced population on Hainan Island. Intensified genetic drift in small and isolated H. hainanensis populations may contribute to moderate differentiation between some of them, as revealed by pairwise Fst. In conclusion, our conservation genomic study confirms severe population decline and extremely low level of nucleotide variation in H. hainanensis on Hainan Island. These findings provide critical insights for the sustainable management and genetic restoration of H. hainanensis on Hainan Island.